Doing natural theology consistently with theism and why one might stop trying - Mawson, T (Cambridge University Press, 2017)
Theists such as Swinburne who seek to use natural theological arguments to move from observations about the world to conclusions about the existence (or probable existence) of God seem to need premises concerning what the world would have been like were Theism to have been false, viz. premises to the effect that it would have been (or would probably have been) different from the way we observe the actual world to be. Surely only that way could observations of the actual world be taken to be evidence that Theism is true. 1 And surely for such arguments to be dialectically powerful in discussions with Atheists, these premises need to be acceptable to Theists and Atheists alike. 2 In this article, I call these claims into question.